GJB1 mutation screening and in vitro investigation of its upstream mutations - Arı, Oğuz. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2017., 2017)
Charcot-Marie-Tooth Type 1X (CMTX1) is the X chromosome linked form of the disease and caused by mutations in the gap junction protein 1 (GJB1) gene. This gene is the second most commonly mutated gene in all CMT forms after PMP22 gene duplication and covers 10% of all CMT cases. More than 400 different mutations have been identified in all regions of this gene, up to date. All types of mutations such as missense, nonsense, splice site mutations, small insertions, deletions leading to formation of truncated protein were reported and some rare patients have whole gene deletions. Variants in 5’ promoter region were reported in a few patients. These variants are expected to reduce the gene expression level and cause loss of function. In previous years, two novel upstream mutations (c.-541A> G and c.-528T> C) were identified in our lab. In this study, we screened 50 patients from our Turkish CMT cohort for GJB1 mutations using PCR and direct sequencing strategy. Eight different variants were identified in GJB1 including three 5’ UTR variants. Among them, two coding region and one upstream variants were novel mutations. In the second part, we investigated the effects of 5’ mutations that were identified in our lab, using luciferase reporter gene assay by expressing these GJB1 upstream variants (c.-18A>G, c.-541A> G, c.-528T> C and c.-713G>A) in HEK293T cells. The c.-541A> G and c.-528T> C mutations are located inside the promoter of GJB1 gene and caused significant reduction in gene expression level providing evidence for the loss of function effect of these variants. The c.-18A>G variant was also shown to cause a slight decrease in gene expression. It is located in a splice site of the gene and possibly responsible for abnormal protein production. Lastly, c.-713G>A which was previously reported as a polymorphism caused no significant effect on luciferase expression. This study contributed to molecular diagnosis of CMTX1, described a common upstream variant in our CMT population, and demonstrated reduced gene expression effect for three novel upstream variants.
Keywords: Gap junctions (Cell biology); Molecular genetics.; Genetics -- Technique.